STRATEGI PENGEMBANGAN AGROINDUSTRI TEMPE DI KECAMATAN BALIK BUKIT KABUPATEN LAMPUNG BARAT - Nuraini Nuraini; Ktut Murniati; Lina Marlina (Journal of Food System & Agribusiness, 2021)
The study aims to analyze the development strategy for the tempe agroindustry.  This research uses survey method at Sebarus District, Balik Bukit Regency, West Lampung purposively.  The data collected in March 2020.  The data were analyzed by using the IFAS and EFAS matrix and SWOT analysis.  The result showed that tempe agroindustry was in I matrix (growth strategy).  The development strategy were the production of high quality product so tempe is in demand by various society levels, the production of high quality product because of the good technology which makes production time faster, the production of high quality product and the good skills of human resources so product competitiveness is high, and good skills by utilizing support from the government.